Kedudukan Peraturan Daerah Dalam Hierarki Peraturan Perundang-undangan - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2006)
The mechanism procedure of establishing by laws is the same with Act and the posisition of by law is equal with the Act, in the sense, that by laws and Act are legislative products.However, the contain of bylaws is different with the Act The implementation of bylaws is limited to a certain region, otherwise the Act isimplemented in the national level. Thus, the hierarchy ofbylaw is lower than the Act.